2019
DOI: 10.3390/ijms20153781
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Hydrophilic-Hydrophobic Balance of Antigen-Loaded Peptide Nanofibers on Their Cellular Uptake, Cellular Toxicity, and Immune Stimulatory Properties

Abstract: Recently, nanofibers (NFs) formed from antigenic peptides conjugated to β-sheet-forming peptides have attracted much attention as a new generation of vaccines. However, studies describing how the hydrophilic-hydrophobic balance of NF components affects cellular interactions of NFs are limited. In this report, three different NFs were prepared by self-assembly of β-sheet-forming peptides conjugated with model antigenic peptides (SIINFEKL) from ovalbumin and hydrophilic oligo-ethylene glycol (EG) of differing ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 57 publications
(84 reference statements)
0
13
0
Order By: Relevance
“…Previously, we stated that the EG length of NFs significantly influences their cellular association and toxicity [ 40 ]. For further understanding on the effect, we investigated herein the interactions between the DPPC Langmuir membrane and three types of NFs with different EG lengths (6-, 12- and 24-mer).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we stated that the EG length of NFs significantly influences their cellular association and toxicity [ 40 ]. For further understanding on the effect, we investigated herein the interactions between the DPPC Langmuir membrane and three types of NFs with different EG lengths (6-, 12- and 24-mer).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we reported that EG n NFs with shorter EG chains were more efficiently associated with JAWS II cells and exhibited higher cytotoxicity [ 40 ]. The EG-length dependency for cellular interaction had the same tendency as that for the interaction with the DPPC membrane.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations